The origin and development of the Center for Interdisciplinary Studies. A historical outline by 1993 - Trombik, Kamil Piotr (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2019)
The paper concerns the origin and early stage of development of the Center for Interdisciplinary Studies at the Pontifical Academy of Theology in Kraków. Center for Interdisciplinary Studies was founded by Michał Heller and Józef Życiński in the late 1970s. It was an informal institution which focused on conducting scientific activity in the area of philosophy of nature, relationship between mathematical & natural sciences and philosophy, history of science, as well as relationships between science and religion. In this paper I would like to present how this institution developed, I will discuss various forms of its activity and discuss—very generally—what kind of philosophy was promoted by M. Heller, J. Życiński as well as their pupils and close associates. An important part of the paper will also concern the Center for Interdisciplinary Studies as a unique institution, which has developed—in difficult historical period in Poland—philosophical research in the spirit of freedom and respect for the new achievements of science, and also promoted interdisciplinary dialogue between scientists and philosophers.
Keywords: Center for Interdisciplinary Studies; Michał Heller; Józef Życiński; history of Polish philosophy; philosophy of nature; philosophy in science